BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Human milk: From complex tailored nutrition to bioactive impact on child cognition and behavior - Carolina de Weerth; Anna-Katariina Aatsinki; Meghan B. Azad; Frank F. Bartol; Lars Bode; Maria Carmen Collado; Amanda M. Dettmer; Catherine J. Field; Meagan Guilfoyle; Katie Hinde; Aniko Korosi; Hellen Lustermans; et al. (Critical Reviews in Food Science and Nutrition, 2023)

The virtual liver: state of the art and future perspectives - Dirk Drasdo; Johannes Bode; Uta Dahmen; Olaf Dirsch; Steven Dooley; Rolf Gebhardt; Ahmed Ghallab; Patricio Godoy; Dieter Häussinger; Seddik Hammad; Stefan Hoehme; Hermann-Georg Holzhütter; et al. (Archives of Toxicology, 2014)